An X-band Reflectarray Antenna with a Meander-Shaped Unit Cell Structure - Singh U.; Bharati R.; Mali R.; Ajitesh; Meshram M.K. (My University, 2025)
The proposed paper describes a meander-shaped reflectarray antenna design for X-band applications with a single layer (no air) structure as it exhibits a small size and large electrical length. The proposed structure has six circles attached with a center at the corner of a hexagonal patch which makes a meander shape. The inter-element spacing is kept as λ/2. The reflection angle range is close to 360° for practical implementation. The aperture for the designed reflectarray is circular. The corresponding dimension of this is kept at 255 mm. It has 225 elements placed into it. This is simulated using CST software The gain of pyramidal horn is 13 dBi for excitation. The maximum Simulated gain is obtained at 21.9 dBi along the broadside at 10.3 GHz. The 3-dB gain bandwidth is 10.4% in the covering frequency band from 9.75GHz to 10.81GHz. The Maximum aperture efficiency of the proposed RA is 21.2%. © 2024 IEEE.